Place and practice: Sexual risk behaviour while travelling abroad among Swedish men who have sex with men. Issue 25 (September 2018) - Persson, Kristina Ingemarsdotter; Berglund, Torsten; Bergström, Jakob; Tikkanen, Ronny; Thorson, Anna; Forsberg, Birger
Abstract: Background: The proportion of newly diagnosed HIV and STI cases among men who have sex with men (MSM) that were contracted abroad has been increasing in Sweden. The present study explored factors associated with casual unprotected anal intercourse (UAI) and travelling abroad among MSM. Methods: A cross-sectional stratified survey with 2751 MSM was conducted. The frequency of sexual practices among men who had casual UAI abroad (<12 months) with that of men who had casual UAI only in Sweden were compared and factors associated with casual UAI abroad were identified through regression analysis. Results: Factors associated with casual UAI abroad within the previous 12 months were: visit a gay sauna (OR 6.15, 95% CI 3.43–11.06), visit gay café/bar/pub (OR 3.24, 95% CI 1.62–6.48), experience of UAI with a foreign visitor (OR 4.80, 95% CI 2.37–9.75), living with HIV (OR 2.73, 95% CI 1.15–6.48), reporting poor overall health (OR 2.24, 95% CI 1.13–4.44), being born outside Sweden (OR 2.21, 95% CI 1.08–4.53), and being vaccinated against hepatitis A, hepatitis B, or both (OR 1.92, 95% CI 1.13–3.27). Conclusion: MSM who engage in casual UAI abroad need to increase their understanding of related risks and that risk varies with place and practice. Health care professionals should address the preventive needs of traveling MSM and offer counselling and STI-preventive measures.